2013
DOI: 10.1007/s11356-013-1851-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the effects of nickel on benthic macroinvertebrates in the field

Abstract: A field-based evaluation of the biological effects of potential nickel (Ni) exposures was conducted using monitoring data for benthic macroinvertebrates and water chemistry parameters for streams in England and Wales. Observed benthic community metrics were compared to expected community metrics under reference conditions using RIVPACS III+ software. In order to evaluate relationships between Ni concentrations and benthic community metrics, bioavailable Ni concentrations were also calculated for each site. A l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 15 publications
5
29
1
Order By: Relevance
“…Since no major point sources of Cu and Zn emissions were located in the vicinity of the study sites, we believe that the levels of these metals reflect inputs from AF paints used on leisure boat hulls. Several studies have also shown a metal release from AF paints in marinas [8,47,48] Such elevated metal concentrations can impact various species inhabiting harbour areas, including snails [49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…Since no major point sources of Cu and Zn emissions were located in the vicinity of the study sites, we believe that the levels of these metals reflect inputs from AF paints used on leisure boat hulls. Several studies have also shown a metal release from AF paints in marinas [8,47,48] Such elevated metal concentrations can impact various species inhabiting harbour areas, including snails [49,50]. …”
Section: Discussionmentioning
confidence: 99%
“…The Guadalquivir River basin was particularly affected by this element. An excess of Ni have been found to affect survival of algae (Eisler, 1998;Muyssen et al, 2004) and also of some freshwater gastropod species (Peters et al, 2014;Niyogi et al, 2014). The toxicity of Cu and Zn, can be explained by their bactericidal and antimicrobial nature affecting the enzymatic systems.…”
Section: Discussionmentioning
confidence: 99%
“…As long ago as 1998 (Warne, 1998) Field-based and functionality-based SSDs may be used to derive WQGs or to provide lines of evidence in weight-of-evidence based approaches (Peters et al 2010;Peters and Simpson 2012). Field-based methods have been developed in the U.S. and Great Britain (Linton et al 2007;Peters et al 2010;Peters et al 2011), but they are new and have not been widely adopted and perhaps should play a greater role in WQG derivation or validation. In Australia and New Zealand (ANZECC/ARMCANZ, 2000a,b), unlike in other jurisdictions the highest quality WQGs are considered to be those derived directly using field, meso-or microcosm derived data, although, as yet, there are no such instances of guidelines being derived on this basis.…”
Section: Deriving Wqgs For Ecosystem Protectionmentioning
confidence: 99%
“…There are several examples of using these types of data to validate WQGs Linton et al 2007;Peters et al 2010). The applicability of such tools and approaches outside Europe and the US, however, requires further investigation.…”
Section: Validation Of Water Quality Guidelinesmentioning
confidence: 99%